Escola italiana de história das religiões: o legado do método histórico comparativo Pettazzoniano entre seus sucessores - Costa, Márcia Maria Enéas (2023)
Raffaele Pettazzoni was an Italian historicist who his entire life to the study of religions, leaving as his main legacy the Comparative Historical Method, his approach to the world of religions which even today stimulates academic debates in the area. In this sense this study has tried to detect which of the main disciples of Raffaele Pettazzoni (Angelo Brelich, Ernesto de Martino and Ugo Bianchi) mostly approached his Historical Comparative Method. In view of this, we deepened the development of the Method followed by these disciples —academic scholars who, starting from their own concepts, gave a new interpretation to their master's Method, being directed, each one of them, by various biases in their appreciation of the object religion. In other words, we have developed a comparative analysis of the concepts considered key in the Comparative Method developed by these disciples directly influenced by Pettazzoni, a group of scholars who in the second half of the 20th century became known as the Italian School of History of Religions. We consequently specifically focus on the conceptual formation developed by Ugo Bianchi, whom we theorize to be probably the author who followed most faithfully the perspective of his own mentor. To this aim we pursue the following specific objectives: to describe the development process of the Comparative Method in its origins, from its creator, Raffaele Pettazzoni, and the result of his academic journey; to discuss the different approaches to the Comparative Method from the perspective of the members of the Italian School of History of Religions starting with Angelo Brelich, Ernesto de Martino and Ugo Bianchi. Finally, a comparison was made between the concepts considered key to the Comparative Method by Raffaele Pettazzoni and those maintained by Angelo Brelich, Ernesto de Martino and Ugo Bianchi, highlighting similarities and differences. That said, to achieve our objective, we have drawn on bibliographic research, as well as on interviews with second and third generation professors at the Italian School and some of its best-known critics, applying the dialectical and comparative method, through which we found methodological support that we needed. Therefore, it is through detailing the thought of these four authors that we intend to prove our thesis, that is, that Ugo Bianchi was, among the scholars who took advantage of Pettazzoni's seminal theoretical thought, the one who came closest to his methodology.